Antibiotic prophylaxis and hospitalization of horses subjected to median laparotomy: gut microbiota trajectories and abundance increase of Escherichia - Kauter, Anne; Brombach, Julian; Lübke-Becker, Antina; Kannapin, Dania; Bang, Corinna; Franzenburg, Sören; Stoeckle, Sabita D.; Mellmann, Alexander; Scherff, Natalie; Köck, Robin; Guenther, Sebastian; Wieler, Lothar H.; et al. (Frontiers in Microbiology, 2023)
Horse clinics are hotspots for the accumulation and spread of clinically relevant and zoonotic multidrug-resistant bacteria, including extended-spectrum β-lactamase producing (ESBL) Enterobacterales. Although median laparotomy in cases of acute equine colic is a frequently performed surgical intervention, knowledge about the effects of peri-operative antibiotic prophylaxis (PAP) based on a combination of penicillin and gentamicin on the gut microbiota is limited. Therefore, we collected fecal samples of horses from a non-hospitalized control group (CG) and from horses receiving either a pre-surgical single-shot (SSG) or a peri-operative 5-day (5DG) course of PAP. To assess differences between the two PAP regimens and the CG, all samples obtained at hospital admission (t0), on days three (t1) and ten (t2) after surgery, were screened for ESBL-producing Enterobacterales and subjected to 16S rRNA V1-V2 gene sequencing.We included 48 samples in the SSG (n=16 horses), 45 in the 5DG (n=15) and 20 in the CG (for t0 and t1, n=10). Two samples from of equine patients horses undergoing receiving antibiotic treatment prophylaxis (6.5%) were positive for ESBL-producing Enterobacterales at t0, while this rate increased to 67% at t1 and decreased only slightly at t2 (61%). Shannon diversity index (SDI) was used to evaluate alpha-diversity changes, revealing there was no significant difference that between horses suffering from acute colic seemed to have a compromised fecal microbiota composition (5DG, SDImean of 5.90; SSG, SDImean of 6.17) when compared to the CG (SDImean of 6.53) at t0, although the difference lacked significance. Alpha-diversity decreased significantly in both PAP groups at t1, while at t2 the onset of microbiome recovery was noticed. Although we did not identify a significant SDImean difference with respect to PAP